Financing Late Industrialization: Evidence from the State Bank of the Russian Empire - Suesse, Marvin (My University, 2025)
Gerschenkron (1962) argued that public institutions such as the State Bank of the Russian Empire spurred the country’s industrialization. We test this assertion by exploiting plant-level variation in access to State Bank branches using a unique geocoded factory data set. Employing an identification strategy based on geographical distances between banks and factories, our results show improved access to public banking encouraged faster growth in factory-level revenue, mechanization, and labor productivity. In line with theories of late industrialization, we also find evidence that public credit mattered more in regions where commercial banks were fewer and markets were smaller.
PUBLISHED
Keywords: International Development; International Integration